Implementasi Pelaporan, Kejelasan Sasaran Anggaran, Pengendalian Intern terhadap Akuntabilitas Kinerja Instansi Pemerintah: Studi Kasus Organisasi Perangkat Daerah Kota Yogyakarta - Kurnia Herawati, Venta; Widodo, Sri (PRIVE: Jurnal Riset Akuntansi dan Keuangan, 2024)
The purpose of study to examine implementation of reporting, clarity of budget target, internal control on performance accountability of government agencies in Yogyakarta City Regional Apparatus Organizations. The formulation of research problem is influence the application of public sector accounting reporting on government performance accountability, effect of budget target clarity on government agency performance accountability, effect of internal control on government agency performance accountability. Collecting research data use purposive sampling technique. This type research is quantitative. Data collection use a questionnaire and 53 respondents consisting of heads of offices, heads of finance, and financial staff in 18 Regional Organizations of the City of Yogyakarta. The data analysis use multiple linear analysis with SPSS 25 application. The result show public sector accounting reporting has a positive effect in government agency performance accountability, clarity budget target has positive effect on government agency performance accountability, and internal control has an effect on government agency performance accountability.